Socioeconomic Status and Hypertension among Teachers and Bankers in Addis Ababa, Ethiopia - Girma Fikadu; Seblewengel Lemma (International Journal of Hypertension)
Background. The social and economic changes taking place in developing countries are influencing the pace at which hypertension and its risk factors are expanding. As opposed to the already established inverse association in developed nations, the association between socioeconomic status and hypertension in developing countries is poor and inconsistent. This study aims to determine the association between socioeconomic status and hypertension among teachers and bankers in Addis Ababa, Ethiopia. Methods. This study is based on a cross-sectional study conducted to assess the prevalence of NCDs in Addis Ababa, Ethiopia. The study was undertaken among workers of the Commercial Bank of Ethiopia and teachers of public schools in 2010. Results. Majority of participants were teachers (70.3%). Most of the respondents (54.1%) earn an annual income between 15,000 ETB and 48,000 ETB, and 51.9% of them have educational status of first degree and above. Among the socioeconomic factors income was strongly associated with the odds of having hypertension (AOR: 2.17 with 95% CI: 1.58–2.98). Conclusions. Higher burden of hypertension is observed among teachers and bankers in Addis Ababa, Ethiopia. Promotion of healthy behaviors and interventions that target higher income groups needs to be put in place.